2021
DOI: 10.1016/j.cmi.2021.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum to ‘detection of SARS-CoV-2 N-antigen in blood during acute COVID-19 provides a sensitive new marker and new testing alternatives’

Abstract: Clinical Microbiology and Infection xxx (xxxx) xxx Please cite this article as: Le Hingrat Q et al., Corrigendum to 'detection of SARS-CoV-2 N-antigen in blood during acute COVID-19 provides a sensitive new marker and new testing alternatives', Clinical Microbiology and Infection,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Indeed, the sensitivity value of COVID-VIRO on NP samples with Cts ≤33 was 86% (CI 95%: 79−90.5%). These results are comparable to those of Hingrat et al that showed that with high nasopharyngeal viral loads, i.e., Ct values below 30 and 33, only 1/50 and 4/67 tested negative for N-antigenaemia, respectively [ 16 ]. In addition, they have shown this with hospitalized patients with symptoms compatible with SARS-CoV-2 infection, but with a negative nasopharyngeal RT-PCR, 8/12 presented positive N-antigenaemia.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Indeed, the sensitivity value of COVID-VIRO on NP samples with Cts ≤33 was 86% (CI 95%: 79−90.5%). These results are comparable to those of Hingrat et al that showed that with high nasopharyngeal viral loads, i.e., Ct values below 30 and 33, only 1/50 and 4/67 tested negative for N-antigenaemia, respectively [ 16 ]. In addition, they have shown this with hospitalized patients with symptoms compatible with SARS-CoV-2 infection, but with a negative nasopharyngeal RT-PCR, 8/12 presented positive N-antigenaemia.…”
Section: Discussionsupporting
confidence: 88%
“…N-antigenemia levels were determined from serum samples with a CE-IVD ELISA microplate assay, the COV-QUANTO kit (AAZ, Boulogne-Billancourt, France), following manufacturer instructions. This assay has been evaluated elsewhere [ 11 , 16 ]. The cut-off limit was presented at 2.98 pg/mL, according to manufacturer recommendations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 proteins in the blood (antigenemia) of individuals with COVID-19 have been well described in adults but limited data are available for children, in whom clinical manifestations of SARS-CoV-2 infection are more heterogeneous. Viral nucleocapsid antigenemia has been identified as a sensitive and specific biomarker of acute infection, [1][2][3][4][5] and both nucleocapsid and spike antigenemia have been associated with disease severity in adults. [3][4][5] Spike protein antigenemia has also been inconsistently observed in children with SARS-CoV-2 associated multisystem inflammatory syndrome (MIS-C).…”
Section: Introductionmentioning
confidence: 99%
“…Circulation of viral antigens in blood is a mainstay of diagnostic testing in systemic viral infections, for example, HBV and HIV. However, in respiratory infections such as severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), antigenemia in serum is harder to interpret 1,2 . Systemic presence of nucleocapsid (NCP), as well as spike (S) protein, has been described 3 .…”
Section: Introductionmentioning
confidence: 99%